Development of split-force-controlled body weight support (SF-BWS) robot for gait rehabilitation - Takai, Asuka; Teramae, Tatsuya; Noda, Tomoyuki; Ishihara, Koji; Furukawa, Jun-ichiro; Fujimoto, Hiroaki; Hatakenaka, Megumi; Fujita, Nobukazu; Jino, Akihiro; Hiramatsu, Yuichi; Miyai, Ichiro; Morimoto, Jun (Frontiers in Human Neuroscience, 2023)
This study introduces a body-weight-support (BWS) robot actuated by two pneumatic artificial muscles (PAMs). Conventional BWS devices typically use springs or a single actuator, whereas our robot has a split force-controlled BWS (SF-BWS), in which two force-controlled actuators independently support the left and right sides of the user's body. To reduce the experience of weight, vertical unweighting support forces are transferred directly to the user's left and right hips through a newly designed harness with an open space around the shoulder and upper chest area to allow freedom of movement. A motion capture evaluation with three healthy participants confirmed that the proposed harness does not impede upper-body motion during laterally identical force-controlled partial BWS walking, which is quantitatively similar to natural walking.To evaluate our SF-BWS robot, we performed a force-tracking and a split-force control task using different simulated load weight setups (40, 50, and 60 kg masses). The splitforce control task, providing independent force references to each PAM, conducted with a 60 kg mass and a test bench, demonstrates that our SF-BWS robot is capable of shifting human body weight in the mediolateral direction. The SF-BWS robot successfully controlled the two PAMs to generate the desired vertical support forces.